Why do patients decline amniocentesis? Analysis of factors influencing the decision to refuse invasive prenatal testing - Pawel Sadlecki; Marek Grabiec; Pawel Walentowicz; Malgorzata Walentowicz-Sadlecka (BMC, 2018)
Abstract Background In recent years, determination of personalized risk for fetal chromosomal anomalies emerged as an important component of prenatal genetic counseling. Women in whom fetal risk for chromosomal aberrations is elevated are offered further testing. The aim of this study was to identify factors that may influence the decision to refuse invasive prenatal testing aimed at determination of fetal karyotype in a group of patients at increased risk of trisomy 21. Methods The analysis included 177 patients with singleton pregnancy, whose personalized risk score for trisomy 21 calculated on the basis of the combined test exceeded 1:300. Diagnostic amniocentesis was performed in 125 patients from this subset, since the remaining 52 women declined invasive prenatal testing. The following factors were analyzed as potential determinants of the decision to refuse amniocentesis: maternal age (≥35 years), gravidity, number of miscarriages in previous pregnancies, educational status, marital status, indications to prenatal testing, gestational age at the time of prenatal testing, personalized risk score for fetal chromosomal aberrations and nuchal translucency (NT) value. Results A statistically significant relationship was found between the decision to refuse amniocentesis and the number of previous miscarriages, maternal educational level, NT values and personalized risk score for fetal chromosomal aberrations. Multivariate logistic regression analysis identified primary maternal education and history of more than two miscarriages as independent significant predictors of declining amniocentesis. Women with personalized risk scores for trisomy 21 greater than 1:100 opted out of invasive prenatal diagnosis significantly less often than the remaining participants. Conclusion In conclusion, the key role of high quality and accuracy of non-invasive diagnostic tests conducted in the first trimester should be emphasized as personalized risk score for fetal chromosomal aberrations determined based on their results is pivotal for further management of pregnancy. Equally important is to provide the patients with an accurate and comprehensible information about potential benefits and risks of invasive testing.